On the Vortex Detection Method Using Continuous Wavelet Transform with Application to Propeller Wake Analysis. (16th June 2015) - Wang, Lifeng; Hu, Ruifeng; Zhang, Jun; Ma, Yunpeng
Abstract : The method based on the continuous wavelet transformation to detect and characterize two-dimensional vortex is analyzed for a synthetic flow and applied to vortex detection of propeller wake. The characteristics of a vortex, such as center location, core radius, and circulation, are extracted based on the Lamb-Oseen and Rankine vortex models, the latter of which is a novel attempt. The effects of various factors such as the difference scheme, the grid and scale discretization, transform variable, and vortex model on vortex detection have been investigated thoroughly. The method is further applied to identify the tip vortex in a propeller wake.